Sun-induced synchronizations of the interannual to interdecadal hemispheric mean (land and sea) temperature variations. (December 2020) - Sonechkin, Dmitry M.; Vakulenko, Nadezda V.; Volodin, Evgeny M.
Abstract: Some hemispheric variation features of the near surface air and sea-surface temperatures are considered. A specially designed technique of the wavelet-based cross-correlations is used for this purpose. In-phase synchronizations of the hemispheric temperatures as whole as well as such synchronizations between land and sea temperatures are found within the timescales of one, two, and six-seven decades. In contrast, no synchronization is found within the timescales between the above indicated ones. Consideration of the afore-mentioned temperatures in a long integration of the climatic model of the Marchuk Institute of Numerical Mathematics of RAS (the "Pi-Control" experiment when external forces were accepted equal to their mean values during the preindustrial period) shows lack of any synchronization. However, results of the "Historical" experiment when effects of external forces, and, in particular, small variations of the total solar irradiation (TSI), were taken into consideration, reveal similar in-phase synchronizations in the same timescales in which the in-phase synchronizations exist in reality, but during the second half of the XXth century only. Perhaps, it is so because the TSI effects were taken into consideration incorrectly for the first half of the XXth century. All (in reality and in the model runs as well) synchronized temperature variations lag respective TSI variations. From this one can suppose that the namely TSI-variations, despite their amplitudes are very small, synchronize the hemispheric temperature variations. Graphical abstract: Image 1 Highlights: The interhemispheric in-phase synchronization of the mean (land and sea) temperature variations was revealed. The existence of the interhemispheric in-phase synchronization is supported by a climatic model run. Small variations of the total solar irradiation are taken into consideration in this climatic model.